Influence of the Compression Ratio and Duration Injection on Performance and Emission of Sinjai Engine Type Flexible Fuel Engine 150 cc Fueled Bioethanol E70 - Hanapi Hasan; Bambang Sudarmanta; Marthen Paloboran (Institut Teknologi Sepuluh Nopember, 2017)
In this study, the effects of using gasoline (E0) and gasoline-ethanol blends E70 on engine performance and exhaust emissions have been experimentally investigated. The investigation was conducted on a single-cylinder, four-stroke, spark ignition engine. The experiments were performed by varying the compression ratio and duration injection (100%, 125%, 150%, 175% and 200%) at a speed of 2000 up to 8000 rpm at full open throttle. The experimental results showed that blending gasoline with ethanol slightly increased the torque and decreased carbon monoxide (CO) and hydrocarbon (HC) emissions. It was also found that blending with ethanol allows increasing the compression ratio without knock occurrence.